Specificity of Managing a Network Educational Program for Creative Specialist Training - Y. Medvedeva , Tatyana; V. Daricheva, Maria; V. Nikolina, Vera; A. Sizova, Olga; A. Kazantseva, Galina; A. Karpukova, Albina (International Journal of Psychosocial Rehabilitation, 2020)
The urgency of studying the conditions of efficiency in managing an educational program is associated with key problems in developing an educational product as well as objective laws in functioning of the program. The goal of the research is to study the process of managing a network educational program for the specialty Producer Business. The main method of the research on the topic is the analysis of the conditions for the implementation of the network educational program for the specialty Producer Business. The results of researching the problems of the proficiency of future media specialists in view of the dynamic digitalization in the society have determined the demanded competencies as well as the students’ attitude towards opportunities of increasing their personal capabilities in professional activity. The research data can be used in organizing educational program management implemented in a network form.